Molecular and haematological characterization of deletional alpha thalassemia in northeastern Malaysia - Bahar, Rosnah; Sahid, Salman Mohd; Ramli, Marini; Noor, Noor Haslina Mohd; Yusoff, Shafini Mohamed; Arifin, Samilawati Mohd; Zulkafli, Zefarina (Bangladesh Journal of Medical Science, 2023)
Background: Alpha (α) thalassemia is an inherited condition that often cause public health problem in Malaysia. Thalassemia screening program plays extremely important roles for early detection. Therefore, it is important to accurately characterized molecular and hematologic parameters to determine the carrier genotype and prevent thalassaemia major or intermedia offspring. Objective: The objective of this study is to detect α-globin gene deletions and evaluate the haematological parameters among deletional α thalassemia patients in Hospital Universiti Sains Malaysia, Northeastern Malaysia. Result: 71 (33.2%) out of of 214 samples in this study, were detected with α thalassaemia deletional type. South-East Asian (SEA) (50.7%) was most common type α deletional thalassaemia detected. There was a significant difference between the median of Hb, MCV and MCH level of patients with and without α deletion. Conclusion: This study highlighted the importance of hematological parameter as well as Hb analysis to be used as a guide before proceed with molecular method in establishing a definitive diagnosis for proper management. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 410-415